Carbonate veins trace seawater circulation during exhumation and uplift of mantle rock: Results from ODP Leg 209 - Bach, Wolfgang; Rosner, Martin; Jöns, Niels; Rausch, Svenja; Robinson, Laura F.; Paulick, Holger; Erzinger, Jörg (Earth and Planetary Science Letters, 2011)
Carbonate veins hosted in ultramafic basement drilled at two sites in the Mid Atlantic Ridge 15°N area record two different stages of fluid-basement interaction. A first generation of carbonate veins consists of calcite and dolomite that formed syn- to postkinematically in tremolite–chlorite schists and serpentine schists that represent gently dipping large-offset faults. These veins formed at temperatures between 90 and 170 °C (oxygen isotope thermometry) and from fluids that show intense exchange of Sr and Li with the basement (87Sr/86Sr = 0.70387 to 0.70641, δ7LiL-SVEC = + 3.3 to + 8.6‰). Carbon isotopic compositions range to high δ13CPDB values (+ 8.7‰), indicating that methanogenesis took place at depth. The Sr–Li–C isotopic composition suggests temperatures of fluid-rock interaction that are much higher (T > 350–400 °C) than the temperatures of vein mineral precipitation inferred from oxygen isotopes. A possible explanation for this discrepancy is that fluids cooled conductively during upflow within the presumed detachment fault. Aragonite veins were formed during the last 130 kyrs at low-temperatures within the uplifted serpentinized peridotites. Chemical and isotopic data suggest that the aragonites precipitated from cold seawater, which underwent overall little exchange with the basement. Oxygen isotope compositions indicate an increase in formation temperature of the veins by 8–12 °C within the uppermost ~ 80 m of the subseafloor. This increase corresponds to a high regional geothermal gradient of 100–150 °C/km, characteristic of young lithosphere undergoing rapid uplift.
id: 2162